(untitled) (Patan Pragya, 2019)
The focus of this paper is to analyze the role of micro-finance in socio-economic development of Kathmandu. Microfinance is a simple but effective credit tool that enables the most poor to pull themselves out of poverty. The socio-economic status of loanees has improved consequently than when they started small business with loan in the earlier days. Moreover, it was found that their socio-economic status was higher than that of non-loanees. Microcredit is an effective tool for raising the socio-economic status of the poor people, particularly the women.